La calidad del empleo en la población afrodescendiente Colombiana: Una aproximación desde la ubicación geográfica de las comuna (2014)
This article builds a compound indicator about job quality using the principal component method for the African-Colombian population resident in Cali, starting from a representative survey carried over in all city districts or “Comunas” by the Colombian Labor Ministry. Cali being the city bearing the largest proportion of Afro-descendant population in Colombia, and the second largest Afro-descendant population in Latin America after Salvador Bahia in Brazil constitutes a model for the working conditions of the Afro-descendant population in Colombia. The results show that African-Colombians living in the east side of the city, composed by districts or “Comunas” 7, 13, 14, 15 and 21 have a higher probability of having low-quality jobs, generating city areas linked to job quality. The college degrees increase the probability of finding high-quality jobs. © Revista de Economía del Rosario.